2017
DOI: 10.1016/j.combustflame.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of BAM:Eu2+ particles as a tracer for temperature imaging in flames

Abstract: The capabilities of the joint temperature-velocity imaging technique, thermographic particle image velocimetry (TPIV) are examined in H 2 laminar diffusion flames, by seeding the fuel stream with BAM : Eu 2+ particles. The upper measurable temperature is found to be 900-1000 K. For these phosphor particles this limit is primarily imposed by thermal quenching of the laser-induced luminescence emission that is used for thermometry. Within this limit, the measured temperature distribution quantitatively agrees wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Note that this is not a concern for short residence times of the particles at high temperatures when used in flows. BAM:Eu 2+ was found to have unchanged luminescence properties after exposure to the high-temperature reaction zones of a non-premixed hydrogen flame (0.1 s above 1700 K) [19].…”
Section: Introductionmentioning
confidence: 97%
“…Note that this is not a concern for short residence times of the particles at high temperatures when used in flows. BAM:Eu 2+ was found to have unchanged luminescence properties after exposure to the high-temperature reaction zones of a non-premixed hydrogen flame (0.1 s above 1700 K) [19].…”
Section: Introductionmentioning
confidence: 97%
“…Aerosol phosphor thermometry (APT) is a temperature imaging technique that relies on temperature-dependent, laser-excited luminescence emission from small particles using a scattering-referenced approach. This measurement represented a significant increase in the maximum temperature measured using APT, which previously had been limited to less than 1000 K [3], and demonstrated the potential for APT in combustion-relevant flows. Although the previous Ce:CSSO measurements were successful in increasing the maximum temperature measurable with APT, there were a few drawbacks to the method.…”
Section: Introductionmentioning
confidence: 71%
“…The temperature measurement precision index (standard deviation), s T , is related to the temperature sensitivity and ratio precision index by equation (3). One can relate the ratio precision index to the signal precision indices (s S1 and s S2 ) through first order uncertainty propagation by…”
Section: Apt Diagnostic Performance Predictionsmentioning
confidence: 99%
“…The temperature of a wake flow ranged from 100 • C to 150 • C, while the temperature of a surrounding air was a room temperature. Fond et al [182,234,235] also reported the relationship between the number density of particles, luminescence intensity, and temperature. Van Lipzig et al [188] measured the gas temperature in a high-pressure vessel using BaMgAl 10 O 17 :Eu and evaluated the precision in the measurement, with results showing 30 K at 393 K and 60 K at 650 K. Lee et al [169] measured the turbulent heat flux in a non-reacting round jet, also using BaMgAl 10 O 17 :Eu.…”
Section: Gaseous Flowmentioning
confidence: 99%